PENYULUHAN PROTOKOL KESEHATAN COVID-19 DAN PEMBAGIAN MASKER KEPADA MASYARAKAT DI WILAYAH KECAMATAN LANGSA BARO KOTA LANGSA PROPINSI ACEH - Putri Nahrisah; Putri Riskina; Chairul Vidya; Ayu Irmayana Siregar (Bajang Institute, 2021)
The Covid-19 pandemic that has hit the world, including Indonesia since the beginning of 2020, has made most of the economic activities, education and public services adjusted. The public is directed to carry out activities by implementing the Covid-19 health protocol. Coronavirus disease 2019 (COVID-19) is a respiratory infection caused by an emerging coronavirus that was first recognized as appearing in Wuhan, China, in December 2019. Genetic sequencing of this virus indicates that it is a betacoronavirus closely related to the SARS virus. This community service is carried out in Langsa Baro District, Langsa City. The method used in the form of